2015
DOI: 10.1073/pnas.1509316112
|View full text |Cite
|
Sign up to set email alerts
|

Turning statistical physics models into materials design engines

Abstract: Despite the success statistical physics has enjoyed at predicting the properties of materials for given parameters, the inverse problem, identifying which material parameters produce given, desired properties, is only beginning to be addressed. Recently, several methods have emerged across disciplines that draw upon optimization and simulation to create computer programs that tailor material responses to specified behaviors. However, so far the methods developed either involve black-box techniques, in which th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 44 publications
1
84
0
Order By: Relevance
“…More recently, design approaches using inverse methods have been implemented. [8][9][10][11]18 In these cases, the forward simulation consists of a numerical engine to solve various trial morphologies by implementing, e.g., a self-consistent field theory, 69 a mean field model based on the Cahn-Hilliard equation, 10 or a theoretically informed coarse-grain model for block copolymers. 70 As before, the forward simulation is coupled to an inverse process that optimizes the parameter set in order to achieve a solution that closely approximates the targeted design.…”
Section: Directed Self-assembly Of Block Copolymer Thin Filmsmentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, design approaches using inverse methods have been implemented. [8][9][10][11]18 In these cases, the forward simulation consists of a numerical engine to solve various trial morphologies by implementing, e.g., a self-consistent field theory, 69 a mean field model based on the Cahn-Hilliard equation, 10 or a theoretically informed coarse-grain model for block copolymers. 70 As before, the forward simulation is coupled to an inverse process that optimizes the parameter set in order to achieve a solution that closely approximates the targeted design.…”
Section: Directed Self-assembly Of Block Copolymer Thin Filmsmentioning
confidence: 99%
“…70 As before, the forward simulation is coupled to an inverse process that optimizes the parameter set in order to achieve a solution that closely approximates the targeted design. In this regard, our recent work 10,11,18 has shown that evolutionary strategies such as CMA-ES can be significantly faster and more efficient in finding optimized solutions than inverse methods based on Monte Carlo searches. 8,9 In a typical design task corresponding to Fig.…”
Section: Directed Self-assembly Of Block Copolymer Thin Filmsmentioning
confidence: 99%
See 3 more Smart Citations